The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1042/bsr20190372
|View full text |Cite
|
Sign up to set email alerts
|

The role of FOXD2-AS1 in cancer: a comprehensive study based on data mining and published articles

Abstract: Background and Aims: Long noncoding RNA FOXD2 adjacent opposite strand RNA 1 (FOXD2-AS1) is aberrantly expressed in various cancers and associated with cancer progression. A comprehensive meta-analysis was performed based on published literature and data in the Gene Expression Omnibus database, and then the Cancer Genome Atlas (TCGA) dataset was used to assess the clinicopathological and prognostic value of FOXD2-AS1 in cancer patients. Methods: Gene Expression Omnibus databases of microarray data and publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Moreover, MINCR is also overexpressed in hepatocellular carcinoma and gall bladder cancer, and its overexpression promotes cell proliferation, migration, and invasion [ 37 , 38 ]. The lncRNA FOXD2-AS1 is abnormally expressed in a number of cancers and affects tumor progression [ 39 ]. Ni et al revealed that FoxD2-AS1 regulates the miR-185-5P/HMGA2 axis and the PI3K/AKT signaling pathway to promote glioma progression [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MINCR is also overexpressed in hepatocellular carcinoma and gall bladder cancer, and its overexpression promotes cell proliferation, migration, and invasion [ 37 , 38 ]. The lncRNA FOXD2-AS1 is abnormally expressed in a number of cancers and affects tumor progression [ 39 ]. Ni et al revealed that FoxD2-AS1 regulates the miR-185-5P/HMGA2 axis and the PI3K/AKT signaling pathway to promote glioma progression [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…LINC00460 was usually upregulated in cervical cancer tissues and cell lines, knockdown of LINC00460 restrain cervical cancer cell growth and invasion in vitro and attenuated tumorigenesis in vivo [ 17 ]. Overexpressed FOXD2-AS1 is linked to tumor size and TNM stage and a risk factor of OS and disease-free survival (DFS) in cancer patients [ 18 ]. EMX2OS is a key metabolism-related enhancer RNA in KIRC with a favorable impact on survival [ 19 ] and EMX2OS is regulated by TCF12 transcription and co-regulates the proliferation, migration and invasion of prostate cancer cells with FUS protein by activating cGMP-PKG pathway [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, almost all oncogene lncRNAs regulate the cell cycle, promote tumor proliferation, inhibit apoptosis, and induce tumor invasiveness and migration. While lncRNAs such as XIST (162-172), CRDNE (173-179), FOXD2-AS1 (186)(187)(188)(189)(190)(191)(192)(193)(194), ANRIL (195)(196)(197), HOXA11-AS (198)(199)(200)(201)(202)(203), TP73-AS1 (204)(205)(206), and DANCR (207-210) are only known as tumor inducers, the ultimate function of some lncRNAs is controversial. For instance, for MALAT1, NEAT1, and TUG1, both oncogenic and tumor suppressor effects have been reported.…”
Section: Role In Tumor Pathologymentioning
confidence: 99%
“…Prognostic value: Higher expression of NEAT1 (147), XIST (164), CRNDE (173, 179), FOXD2-AS1 (186,189,192,194), ANRIL (196), HOXA11-AS (198)(199)(200)203), TP73-AS1 (204,242),…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation